Very rapid cooling of the energetic pyroclastic density currents associated with the 5 November 2010 Merapi eruption (Indonesia) - Trolese, M. (2020)
Understanding the thermal behavior of pyroclastic density currents (PDCs) is crucial for forecasting impact scenarios for exposed populations as it affects their lethality and destructiveness. Here we report the emplacement temperatures of PDC deposits produced during the paroxysmal explosive eruption of Merapi (Central Java) on 5 November 2010 based on the reflectance of entombed charcoal fragments. This event was anomalously explosive for Merapi, and destroyed the summit dome that had been rapidly growing, with partial collapses and associated PDCs, since October 26. Results show mean reflectance values mainly between 0.17 and 0.41. These new data provide a minimum temperature of the flow of 240–320 °C, consistent with previous estimations determined from independent field, engineering, and medical observations published in the literature for this eruption. A few charcoal fragments recorded higher values, suggestive of temperatures up to 450 °C, and we suggest that this is due to the thermal disequilibrium of the deposits, with larger block-size clasts being much hotter than the surrounding ash matrix. Charring temperatures show no major differences between proximal and distal PDC deposits and are significantly lower than those that may be associated with a fast growing dome dominated by dense and vitric non-vesicular rocks. We therefore infer that the decrease in temperature from that at fragmentation (>900 °C) occurred in the very initial part of the current, <2 km from source. We discuss possible processes that allow the very fast cooling of these energetic PDCs, as well as the conservative thermal behavior shown during the depositional phase, across the entire depositional area.